PENGEMBANGAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MENINGKATKAN PELAYANAN PADA SMA AL-HASRA KOTA DEPOK - Fitriani, Dita Indah Noor; Sutrisno, Joko (Universitas Budi Luhur, 2024)
Good service and satisfaction for parents is of course very important. This includes maintaining good ties between the school and the school regarding form payment confirmation services, reminders of tuition payment due dates, consultations and complaints that provide a sense of comfort regarding school and parents. Customer Relationship Management (CRM) is a business method for establishing bonds with customers and the goal of improving customer service. Customer Relationship Management is used to support businesses in carrying out relationships with customers or even potential customers. Al-Hasra High School is managed by implementing management guidelines based on religion and science. The current service is still less than optimal, schools are still unable to confirm online payment forms and enter data directly, and tuition payments are often delayed due to a lack of payment reminders, and ineffective complaint handling at schools. This research was conducted to collect data at Alhasra High School, Depok City. Depending on the needs of the system being created, discussions to obtain more precise and precise data are combined with data obtained from interviews with deputy principals. Head of academic affairs and school staff who provided suggestions for problems related to the problems faced at Al Hasra High School. This research obtained an E-CRM system to improve services with parents at Al-Hasra High School, consisting of a feature for uploading proof of payment forms, bill reminders SPP payments and can see the status of SPP payments and handle complaints to increase the success of business methods and communication for these parties.